Impact and compensation of sample clock offset in I-CFDMA uplink - Dan DING; Nai-ping CHENG; Yu-rong LIAO (Tongxin xuebao)
To achieve the sample clock synchronization in the interleaved code and frequency division multiple access(I-CFDMA)uplink,the I-CFDMA uplink model was established,and the disturbance of the sample clock offset(SCO)on the system model was discussed,in addition,the signal time shift,phase rotation,multi-user interference(MUI)and inter-carrier interference(ICI)caused by SCO were analyzed quantitatively.On this basis,a compensation method of multi-user SCO was proposed.For one thing,the relevant metric function was modified considering the SCO of each user; for another thing,a multi-user detection(MUD)algorithm based on harmony search was proposed.This algorithm has a higher efficiency than the commonly-used genetic algorithm(GA),as well as a performance approximate to that of optimal detection without SCO but with 1 64 computational burden.The computer simulation results validate the conclusions obtained.